Unifying dark matter and dark energy with non-canonical scalars - Swagat S. Mishra; Varun Sahni (European Physical Journal C: Particles and Fields, 2021)
Abstract Non-canonical scalar fields with the Lagrangian $${{\mathcal {L}}} = X^α - V(φ )$$ L = X α - V ( ϕ ) , possess the attractive property that the speed of sound, $$c_s^{2} = (2\,α - 1)^{-1}$$ c s 2 = ( 2 α - 1 ) - 1 , can be exceedingly small for large values of $$α $$ α . This allows a non-canonical field to cluster and behave like warm/cold dark matter on small scales. We derive a general condition on the potential in order to facilitate the kinetic term $$X^α $$ X α to play the role of dark matter, while the potential term $$V(φ )$$ V ( ϕ ) playing the role of dark energy at late times. We demonstrate that simple potentials including $$V= V_0\coth ^2{φ }$$ V = V 0 coth 2 ϕ and a Starobinsky-type potential can unify dark matter and dark energy. Cascading dark energy, in which the potential cascades to lower values in a series of discrete steps, can also work as a unified model.